2xa-11=-5

Simple and best practice solution for 2xa-11=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2xa-11=-5 equation:


Simplifying
2xa + -11 = -5

Reorder the terms:
-11 + 2ax = -5

Solving
-11 + 2ax = -5

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 2ax = -5 + 11

Combine like terms: -11 + 11 = 0
0 + 2ax = -5 + 11
2ax = -5 + 11

Combine like terms: -5 + 11 = 6
2ax = 6

Divide each side by '2x'.
a = 3x-1

Simplifying
a = 3x-1

See similar equations:

| 5x=48+2x | | (5x+3o)+9o= | | -3(4)+-2=x | | -(x-1)-4(x-3)=58 | | -0.2(-15x-10)=10 | | -7(4)+15=x | | z(2z-9)(z+4)=0 | | x^2+kx-9=0 | | 5=4(x-4)+3-3x | | 30+y=3y | | 12x+4+13x-4=180 | | (m-1)x^2+mx+2m=0 | | n+(n+1)+(n+2)+(n+3)=1368 | | 30+y=6y | | 6x+8-5x=14-15x-16 | | 6x/5+12x=3(5/2) | | 3b^2+20b+31=6 | | x^4+10x^3-59x^2+40x+60=0 | | 12y-8=-4 | | 34x-543=321 | | 2x-34=87 | | 29x^2+10x-21=0 | | 3=3(x-2)+5-2x | | (14y+11)+(-4y-3)= | | 15=5(x+9) | | 13p+16q+p-5q-7p= | | 2x(4x-1)=7 | | (14y+11)+(14y-3)= | | 5-9x=35-23x | | D=Bgx | | 0.8x+6.7=2.3 | | -6x+19+8x+19=-6 |

Equations solver categories